Ankylosing spondylitis and the risk of fracture: results from a large primary care-based nested case-control study. Issue 12 (9th December 2008) - Vosse, D; Landewé, R; van der Heijde, D; van der Linden, S; van Staa, T-P; Geusens, P
Abstract : Background and aims: Ankylosing spondylitis (AS) is associated with bone loss in the vertebrae and an increased prevalence of vertebral fractures, but literature about the magnitude of the risk of fracturing is limited. One retrospective cohort study provided evidence of an increased risk of clinical vertebral fractures but not of non-vertebral fractures. This study further explores the risk of clinical vertebral and non-vertebral fractures in a large population database. Methods: In a primary care-based nested case-control study, 231 778 patients with fracture and 231 778 age- and sex-matched controls were recruited. A history of AS was assessed from the medical records. Odds ratios (OR) and 95% confidence intervals (CI) were calculated after adjustment for medication, other illnesses, smoking and body mass index when known. Results: AS was diagnosed in 758 subjects. The prevalence of AS was 0.18% in patients with fracture and 0.15% in controls. Patients with AS had an increased risk of clinical vertebral fracture (OR 3.26; 95% CI 1.51 to 7.02). The risk of fractures of the forearm and hip was not significantly increased (OR 1.21; 95% CI 0.87 to 1.69 and OR 0.77; 95% CI 0.43 to 1.37, respectively). The risk of any clinical fracture was increased in patients with AS with a history of inflammatory bowel disease (OR 2.79; 95% CI 1.10 to 7.08), whereas it was decreased in patients with AS taking non-steroidal anti-inflammatory drugs (OR 0.65; 95% CI 0.50 to 0.84). The risk was not associated with recent back pain, psoriasis, joint replacement therapy and use of sulfasalazine. Conclusions: Patients with AS have an increased risk of clinical vertebral fracture but not of non-vertebral fractures, while the risk of any clinical fracture is increased in patients with concomitant inflammatory bowel disease. The mechanism by which non-steroidal anti-inflammatory drugs reduce the risk of any clinical fracture warrants further research.